Antioxidant, Antibacterial Activity and GC-MS Analysis of Extract of Giant Forest Ant Dinomyrmex gigas (Latreille, 1802) - Evana - Evana; Pratiwi Pratiwi; Ahmad Fathoni; Oscar Efendi; Andria Agusta (UIN Sunan Gunung Djati Bandung, 2019)
Giant forest ant Dinomyrmex gigas is one of the largest ants species in the world, native to the rain forests of Southeast Asia. It is known that ants have glands that produce chemical compounds that inhibit the growth of microbes. Therefore, it is necessary to deter-mine the antioxidant and antibacterial activities as well as identify the chemical compounds of D. gigas extract. D. gigas was extracted successively with n-hexane, ethanol and methanol. The antioxidant activity was evaluated by determination of the half-maximal inhibi-tory concentration (IC50) values while the antibacterial activities of the extracts were determined by measuring the minimum inhibitory concentration (MIC). The results exhibited that the IC50 values of n-hexane, ethanolic and methanolic extracts were 336.18±0.0984, 89.16±0.0219 and 90.72±0.0894 μg/mL respectively. The ethanolic extract exhibited the highest AAI value (0.34) followed by metha-nolic extract (0.33) and n-hexane extract (0.09). Based on AAI val-ues, the extracts were classified as moderate antioxidants. The best MIC values were 625 μg/mL for both ethanolic and methanolic ex-tracts against S. aureus, while MIC values of all extracts against E. coli were >625 μg/mL. Based on MIC values, all of the extracts presented weak activity against both S. aureus and E.coli. The GC-MS analysis showed that there are up to 30 compounds construct-ed of the ethanolic extract. Three major compounds are ethyl oleate (29.78%), n-hexadecanoic acid (17.54%) and oleic acid (10.65%).